2023
DOI: 10.3390/genes14040779
|View full text |Cite
|
Sign up to set email alerts
|

Children with Early-Onset Psychosis Have Increased Burden of Rare GRIN2A Variants

Abstract: Background: Children and adolescents with early-onset psychosis (EOP) have more rare genetic variants than individuals with adult-onset forms of the illness, implying that fewer EOP participants are needed for genetic discovery. The Schizophrenia Exome Sequencing Meta-analysis (SCHEMA) study predicted that 10 genes with ultra-rare variation were linked to adult-onset schizophrenia. We hypothesized that rare variants predicted “High” and “Moderate” by the Variant Effect Predictor Algorithm (abbreviated as VEPHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Furthermore, the variants rs7206256 and rs11644461 in GRIN2A have been shown to be involved in early onset SCZ in Russian and Serbian populations (Poltavskaya et al, 2021). In an American study that included subjects from diverse backgrounds, it was observed that these identical variants were notably more prevalent in the early onset psychosis group when compared to the control subjects (Hojlo et al, 2023). Although the studies describe variants in GRIN2A to increase SCZ risk they do not specify how these variants affect gene function and expression.…”
Section: Snps In Scz Risk Genes Affecting the Glutamatergic Systemmentioning
confidence: 99%
“…Furthermore, the variants rs7206256 and rs11644461 in GRIN2A have been shown to be involved in early onset SCZ in Russian and Serbian populations (Poltavskaya et al, 2021). In an American study that included subjects from diverse backgrounds, it was observed that these identical variants were notably more prevalent in the early onset psychosis group when compared to the control subjects (Hojlo et al, 2023). Although the studies describe variants in GRIN2A to increase SCZ risk they do not specify how these variants affect gene function and expression.…”
Section: Snps In Scz Risk Genes Affecting the Glutamatergic Systemmentioning
confidence: 99%